Measuring the Social Phobia Fifth-Secondary Stage Female Students (Journal of the College of Education for Women, 2019)
The current research aims to know the measurement of the fifth- secondary stage female students' affliction with the social phobia . The research is confined to General directorate of Education in Baghdad / Al-Karkh/2 / for the academic year 2015-2016 and fifth-secondary stage female students. It has been used descriptive method and exposed theoretical sides and previous studies concerning with the social phobia.The procedures of the research include the application of the social phobia scale on random sample of fifth- secondary stage female students ( both branches scientific and literary). The current study has concluded that the fifth- secondary stage female students have phobia with different levels ( high , very high , medium and low) The current study has displayed singnificant conclusions, recommendations and suggestions.